Clinical Outcomes of Minimally Invasive Surfactant Therapy via Tracheal Catheterization in Neonates with a Gestational Age of 30 Weeks or More Diagnosed with Respiratory Distress Syndrome - Moon Young Seo; Gyu Hong Shim; Myoung Jae Chey (Korean Society of Neonatology, 2018)
Purpose Minimally invasive surfactant therapy (MIST) is currently used as a method of surfactant replacement therapy (SRT) for the treatment of respiratory distress syndrome (RDS) in preterm infants with a gestational age of less than 30 weeks. However, few studies have been conducted on MIST in neonates with a gestational age of 30 weeks or more. In this study, we compared MIST with endotracheal intubation as a rescue SRT for spontaneously breathing neonates with a gestational age of 30 weeks or more who were diagnosed with RDS. Methods We investigated the clinical characteristics of spontaneously breathing neonates admitted to the neonatal intensive care unit of the Inje University Sanggye Paik Hospital from January 1, 2014 to December 31, 2016. These neonates were born at a gestational age of 30 weeks or more and were diagnosed with RDS. The neonates who were administered surfactant by MIST were categorized into the MIST group (n=16) and those who underwent endotracheal intubation were categorized into the control group (n=45). Thereafter, the clinical characteristics between the groups were compared. Results Compared to the control group, the MIST group was less likely to require mechanical ventilation within 72 hours (P<0.001). The frequency of bradycardia during SRT was also low in the MIST group (P=0.033). Conclusion MIST is considered relatively feasible and safe for treating RDS for reducing the need for mechanical ventilation and decreasing the occurrence of bradycardia during surfactant administration in neonates with a gestational age of 30 weeks or more.